ANALISIS MUATAN NILAI KARAKTER PADA CERITA RAKYAT PULAU SUMATRA BERDASARKAN PENGUATAN PENDIDIKAN KARAKTER - Innany Mukhlishina (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2019)
The purpose of this study is to describe the content of character values on the folklore of Sumatra Island based on Strengthening Character Education (PPK). Research data sources are folklore taken from the 34 Most Popular Archipelago Folklore book written by Desy Rachmawati and published by Andaliman Books, 2019, 223 pages. This research use desciptive qualitative approach. Furthermore, the data collected was analyzed with a content analysis model, namely (1) determining and discussing the content of character values on the folklore of Sumatra Island based on Character Education Strengthening (PPK) and (2) summarizing the results of the analysis of character education values in the story. The results of this study are the values of character education contained in the story of the island of Sumatra, among others (1) religious, (2) independent, (3) mutual cooperation, and (4) integrity. Religious character values include the firm sub-values of establishment, sincerity, and protecting the small and marginalized. Independent character values include work ethic (hard work), fighting spirit, and courage. The character values of mutual cooperation include sub-values of cooperation, solidarity, empathy, commitment to joint decisions, and help. Integrity character values include the sub values of honesty, example, loyalty, moral commitment, and responsibility. The value of character education can be obtained through various things, one of which is reading and tradition that develops in the community, namely folklore